2013
DOI: 10.1099/vir.0.052142-0
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Nrf2 expression by human cytomegalovirus infection protects host cells from oxidative stress

Abstract: NF-E2 related factor 2 (Nrf2) is a transcription factor that plays a key role(s) in cellular defence against oxidative stress. In this study, we showed that the expression of Nrf2 was upregulated in primary human foreskin fibroblasts (HFFs), following human cytomegalovirus (HCMV/HHV-5) infection. The expression of haem oxygenase-1, a downstream target of Nrf2, was also increased by HCMV infection, and this induction was suppressed in HFFs expressing a small hairpin RNA (shRNA) against Nrf2. The HCMV-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…These findings are in partially agreement with previous studies in adults [29,30,62], showing that increased levels of OS were associated with CMV infection [29]. These studies have also indicated that OS may importantly drive the CMV reactivation and replication [28,30].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in partially agreement with previous studies in adults [29,30,62], showing that increased levels of OS were associated with CMV infection [29]. These studies have also indicated that OS may importantly drive the CMV reactivation and replication [28,30].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, infection of human foreskin fibroblasts with human cytomegalovirus (HCMV/HHV-5) led to the activation of Nrf2 (81). While a previous study reported that HCMV infection led to an increased level of ROS, Nrf2 activation was not mediated by oxidative stress but was rather due to HCMV gene expression (81,82). Finally, Marburg virus was shown to hijack the Nrf2 pathway through its protein VP-24 (83,84).…”
Section: Discussionmentioning
confidence: 95%
“…HCV activation of Nrf2 was dependent on both oxidative stress and calcium responses (79); 5 distinct HCV proteins (core protein, E1, E2, NS4B, and NS5A) activated Nrf2, and this activation was only partially dependent on ROS production (80). In addition, infection of human foreskin fibroblasts with human cytomegalovirus (HCMV/HHV-5) led to the activation of Nrf2 (81). While a previous study reported that HCMV infection led to an increased level of ROS, Nrf2 activation was not mediated by oxidative stress but was rather due to HCMV gene expression (81,82).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting Nrf2 signaling seems to improve bacterial clearance by alveolar macrophages in patients with chronic obstructive pulmonary disease as well as in a mouse model of P. aeruginosa or nontypeable Haemophilus influenzae (52). For several viruses, the Nrf2-mediated induction of cytoprotective genes has been considered to protect infected cells from oxidative damage (53)(54)(55)(56). A recent study described the direct interaction of a Marburg virus protein with the Nrf2 inhibitor Kelch-like ECHassociated protein 1 to activate the cytoprotective antioxidant response pathway as part of their replication strategy (57).…”
Section: Discussionmentioning
confidence: 99%